FACTORS THAT INFLUENCE THE LEARNING MOTIVATION OF JUNIOR HIGH SCHOOL STUDENTS - Suryajana Setya Handaru; Lilla Maria; Nining Loura Sari (Jurnal Keperawatan Malang, 2022)
Most students have poor achievement not because of inadequate abilities, but because of a lack of interest in learning, so that these students do not try to exert all their abilities in an effort to achieve a goal with the learning process. This study aims to collect articles and analyze what factors are related to students' learning motivation. This study uses a literature review method, articles are searched using the PICOS method with a database, Google Scholar, Science Direct, and ProQuest. The criteria for the articles used are articles published in 5 years before 2021. This literature review is summarized using a narrative method by grouping the extracted data similarly according to the results measured to achieve the objectives, then research reviews that meet the inclusion criteria are collected and a journal summary is made including the names researcher, year of publication, publication, title, research methods and results and database. The results showed that there were ten factors that influenced students' learning motivation, including insomnia, milk intake, pbl method, peers, smartphones for learning media, social networks, excessive use of smartphones, use of HOTS-based worksheets, cognitive reconstruction and the role of teachers as well as parental support. The suggestion for this research is that there is a need for research with more updated articles. Keywords: learning motivation, junior high school students